Protocol for a feasibility study of an Indigenous Medication Review Service (IMeRSe) in Australia. Issue 11 (3rd November 2018) - Wheeler, Amanda J; Spinks, Jean; Kelly, Fiona; Ware, Robert S; Vowles, Erica; Stephens, Mike; Scuffham, Paul A; Miller, Adrian
Abstract : Introduction: The age-adjusted rate of potentially preventable hospitalisations for Aboriginal and Torres Strait Islander people is almost five times the rate of other Australians. Quality use of medicines has an important role in alleviating these differences. This requires strengthening existing medication reviewing services through collaboration between community pharmacists and health workers, and ensuring services are culturally appropriate. This Indigenous Medication Review Service (IMeRSe) study aims to develop and evaluate the feasibility of a culturally appropriate medication management service delivered by community pharmacists in collaboration with Aboriginal health workers. Methods and analysis: This study will be conducted in nine Aboriginal health services (AHSs) and their associated community pharmacies in three Australian states over 12 months. Community pharmacists will be trained to improve their awareness and understanding of Indigenous health and cultural issues, to communicate the quality use of medicines effectively, and to strengthen interprofessional relationships with AHSs and their staff. Sixty consumers (with a chronic condition/pregnant/within 2 years post partum and at risk of medication-related problems (MRPs) per site will be recruited, with data collection at baseline and 6 months. The primary outcome is the difference in cumulative incidence of serious MRPs in the 6 months after IMeRSe introduction compared with the 6 months prior. Secondary outcomes include potentially preventable medication-related hospitalisations, medication adherence, total MRPs, psychological and social empowerment, beliefs about medication, treatment satisfaction and health expenditure. Ethics and dissemination: The protocol received approval from Griffith University (HREC/2018/251), Queensland Health Metro South (HREC/18/QPAH/109), Aboriginal Health and Medical Research Council of New South Wales (1381/18), Far North Queensland (HREC/18/QCH/86-1256) and the Central Australian HREC (CA-18-3090). Dissemination to Indigenous people and communities will be a priority. Results will be available on the Australian Sixth Community Pharmacy Agreement website and published in peer-reviewed journals. Trial registration number: ACTRN12618000188235; Pre-results.